A conceptual framework and architecture for m-governance. (4th May 2020) - Mishra, Shailendra; Singh, Mayank
M-governance mainly facilitates government to public (G2P) and public to government (P2G) communication for better public service in terms of information transmission and dissemination. This research aims to develop a m-governance framework and architecture for mobile governance to enhance the communication services of the University in the domain of Admission, Affiliation, Curriculum, Examination, Result and General Inquiry. Proposed m-governance framework build-up on the basis of Technology Acceptance Model (TAM) and 15 enabler including perceived ease of use, perceived usefulness, perceived access, interpersonal influence, perceived trustworthiness, perceived mobility, transparency of governance, compatibility, flexibility, perceived security, perceived enjoyment, network provider service, completeness of service, location influence in the service and emergency management. Proposed application architecture for mobile governance is beneficial because it allows administrators of the affiliated colleges to use the mobile device of their choice but Android, and it offers a simple solution. The analysis of the data reveals that the administrators as well as academician are inclined to have mobile governance for enhancing the communication services of the higher educational system.